2009
DOI: 10.1158/0008-5472.sabcs-3103
|View full text |Cite
|
Sign up to set email alerts
|

Skin thickness as a measure of breast lymphedema.

Abstract: #3103 Introduction: Lymphedema is well-known in the arm but can also occur in the breast. Diagnosis is currently non-standardized and based on clinical impression. We sought to determine if skin thickness could serve as a useful measure in the diagnosis of breast lymphedema (BLE).
 Methods: Patients undergoing unilateral non-mastectomy procedures were enrolled on this prospective clinical study preoperatively and evaluated for signs and symptoms of lymphedema in the operated breast in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Some have suggested that RT and lymphedema act synergistically to produce the relatively shorter latency period ($7 years) seen with ASB compared to the $10 year latency of radiation-induced soft tissue sarcomas [3,6,8,10,13,38,70,71]. Also, breast lymphedema, generally defined as breast erythema, swelling, heaviness, or based on skin thickness, has not been reliably correlated with SAS and no study has compared SAS in patients with breast lymphedema after RT versus those after RT without breast lymphedema [3,8,15,[71][72][73]. Currently, it is unclear if lymphedema of the extremity or breast increases one's risk of developing ASB.…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested that RT and lymphedema act synergistically to produce the relatively shorter latency period ($7 years) seen with ASB compared to the $10 year latency of radiation-induced soft tissue sarcomas [3,6,8,10,13,38,70,71]. Also, breast lymphedema, generally defined as breast erythema, swelling, heaviness, or based on skin thickness, has not been reliably correlated with SAS and no study has compared SAS in patients with breast lymphedema after RT versus those after RT without breast lymphedema [3,8,15,[71][72][73]. Currently, it is unclear if lymphedema of the extremity or breast increases one's risk of developing ASB.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1 , the total thickness of the epidermis ranges from 0.01 to 0.15 mm, depending on age, gender, lifestyles, regions within the body, and health status. 13 17 The stratum corneum is - to 0.02-mm thick 18 and is made of keratinocytes embedded in a lipid matrix. 19 Along with keratinocytes, other cell types found in the other epidermal sublayers are melanocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound has been used in several studies to identify edematous breasts; 13 , 14 , 15 however, while the reliability of measuring the image has been investigated, 4 the level of reliability of the process in capturing the images is unknown. This is an important step as it informs minimal important difference and can be used to assess responsiveness to treatment.…”
mentioning
confidence: 99%